2017
DOI: 10.1007/s12350-016-0725-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic innervation

Abstract: The autonomic nervous system plays a key role in regulating changes in the cardiovascular system and its adaptation to various human body functions. The sympathetic arm of the autonomic nervous system is associated with the fight and flight response, while the parasympathetic division is responsible for the restorative effects on heart rate, blood pressure, and contractility. Disorders involving these two divisions can lead to, and are seen as, a manifestation of most common cardiovascular disorders. Over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 115 publications
0
24
0
3
Order By: Relevance
“…is impairment occurs through an imbalance in the autonomic nervous system (ANS), especially in increased sympathetic modulation and decreased vagal tone leading to decreased heart rate variability (HRV) [5,7,10]. e measurement of these patterns can provide a sensitive and early indicator of serious health impairment in obese individuals with a higher risk of multimorbidity and early mortality [9], as they can be indicators of risk of death and cardiovascular disease [2,11,12], such as coronary artery disease, myocardial infarction, sudden death, heart failure and arrhythmias [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…is impairment occurs through an imbalance in the autonomic nervous system (ANS), especially in increased sympathetic modulation and decreased vagal tone leading to decreased heart rate variability (HRV) [5,7,10]. e measurement of these patterns can provide a sensitive and early indicator of serious health impairment in obese individuals with a higher risk of multimorbidity and early mortality [9], as they can be indicators of risk of death and cardiovascular disease [2,11,12], such as coronary artery disease, myocardial infarction, sudden death, heart failure and arrhythmias [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…5,13 Cardiac autonomic nervous dysfunction may participate in various cardiac pathological processes. 15,16 Generally, the decrease in sympathetic activity or increase of vagus activity will offer a beneficial effect on cardiovascular function. 32 Our previous studies demonstrated that CIHH protects the heart against ischaemia/reperfusion or hypoxia/reoxygenation injury, and CIHH inhibits cardiac β-adrenergic receptor activity in papillary muscle, which suggests that the cardioprotection of CIHH may be correlated with a decrease in sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac autonomic nerve regulation plays an important role not only in maintaining normal cardiovascular function, but also in response to hypoxia, 13,14 and may also participate in various cardiac pathological processes, such as heart failure. 15,16 Our previous studies showed that CIHH inhibits cardiac β-adrenergic receptor activity in papillary muscle, hinting that the cardioprotection of CIHH may be correlated with cardiac autonomic regulation. 5 However, it is not clear whether CIHH affects the regulation of cardiac autonomic nervous system, including the sympathetic nervous system and vagus nerve.…”
mentioning
confidence: 99%
“…Myocardial sympathetic nerve function may be assessed by scintigraphy with iodine-123 MIBG (I-123 MIBG), a norepinephrine analog possessing identical mechanisms of storage, uptake, and release in neurons. Reduced I-123 MIBG uptake in the myocardium, regional defects, or a higher washout of I-123 MIBG 41,[82][83][84][85][86] correlates with myocardial sympathetic dysfunction, however, warrants further investigation before routine clinical use.…”
Section: Small Fiber Neuropathymentioning
confidence: 99%